The influence of deformation on barbell mechanics during the clean pull - Chiu, L. Z. F.; Schilling, B. K.; Fry, A. C.; Salem, G. J. (Sports Biomechanics, 2008)
For simplicity of biomechanical analyses, the weightlifting barbell is typically modelled as a rigid, non-deformable object. Most coaches and weightlifters, however, are aware of the elastic nature of the barbell, and its influence on the successful completion of lifting attempts. Variables such as velocity, work performed, and power output are indicators of the quality of performance during the snatch, clean, and related weightlifting pulling movements. The aim of this study was to establish whether differences exist in determining these biomechanical parameters when the centre of the barbell is analysed compared with each end of the barbell. Nine men performed three maximal-effort repetitions in the clean pull exercise at 85% of their self-reported single repetition maximum (1-RM) clean (90-155 kg) using a barbell instrumented for mechanical analysis. Results indicated that peak barbell speed was 5-30% (P < 0.05) lower for the centre of the barbell than the ends. Although differences (P < 0.05) in kinetic and potential energy were found between the centre and ends of the bar, differences between total work performed were small ( < 6%; P < 0.05) and no differences were observed for average power (P > 0.05). Although approximately the same work and power occur for the centre and ends of the barbell, they manifest as different kinematics as a result of the elastic nature of the equipment. The elastic characteristics should be considered when selecting instrumentation and variables for research involving barbells. Coaches should be aware of the elasticity of barbells, including selecting appropriate viewing angles as well as understanding how deformation may affect the ends of the barbell relative to the centre.